Internet censorship detected in UAE (United Arab Emirates) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in United Arab Emirates. Data sourced from CensoredPlanet.
Censorship Incident ID: AE-2026-0250. Severity: critical. Confidence: 65%